Neurobehavioral Effects of Levetiracetam in Brain Tumor Related Epilepsy - Bernett, Abigail; Phenis, Richard; Fonkem, Ekokobe; Aceves, Jose; KIRMANI, BATOOL F.; Cruz-Laureano, Daniel (Frontiers in Neurology, 2013)
The neurobehavioral profile of antiepileptic drugs (AEDs) has been a recurrent research topic in the scientific literature. As pharmacological treatments for epilepsy continue to evolve, there is a general consensus that newer AEDs have less detrimental side effects in comparison to their older counterparts. Among newer AEDs and epilepsy patients, potential risk for neurobehavioral changes has been reported with levetiracetam. Conversely, limited data exists regarding the manifestation of this symptomatology in a subgroup of epilepsy patients with brain tumors. The current paper reviews the literature regarding the neurobehavioral profile of levetiracetam in brain-tumor related epilepsy and suggestions for future research will be discussed.